"We have to help each other heal": The path to recovery and becoming a professional peer support. Issue 2 (17th February 2016) - Mendoza, Natasha S.; Resko, Stella; Wohlert, Beverly; Baldwin, Adrienne
ABSTRACT: Over the past decade, the peer support role in the treatment of substance use disorders has become increasingly formalized. With the growing popularity of peer support interventions, it is imperative to understand the unique role of peer support specialists (PSSs). The current study is focused on women's roles as PSSs. Understanding women's paths toward their peer support work through their experiences is essential for the continued formalization of peer support interventions designed for women working in gender-specific community-based treatment settings. The major aim of this study was to explore and describe how female PSSs working in a gender-specific treatment setting evolved from being in recovery to coaching recovery. We conducted in-depth qualitative interviews to examine PSS's experiences and attitudes toward their work. Results reinforced prominent feminist psychological developmental theory, an important implication for practice.